Multi-plant production planning in capacitated self-configuring two-stage serial systems - Vercellis, Carlo (European journal of operational research, 1999)
This research deals with a capacitated master production planning and capacity allocation problem for a multi-plant manufacturing system with two serial stages in each plant. We consider both cases in which a decoupling buffer is allowed or not between the two stages. Peculiar to the system considered is the capability of dynamically self-configuring its layout when buffering is disallowed, in the sense that, for each production run, different parallel machines in the second stage are grouped together and serially connected to a machine in the first stage. Although setup times and costs are considered negligible in our model, yet binary setup variables are introduced in order to account for minimum lot-sizes. The resulting mixed {0,1} linear programming model is solved by means of LP-based heuristic algorithms. The proposed modeling and solution procedure has been applied to problem instances originating from a real-world application, showing good results in practice.